Operation Cyclone: How the United States Defeated the Soviet Union - Billard Jr, Robert D (URJ-UCCS: Undergraduate Research Journal at UCCS, 2010)
The Soviet-Afghan War was the source of increased hostilities between the United States and the Soviet Union in the 1980s. The purpose of this research is to determine how much influence the United States, through covert operations, had over the Soviet Union. My argument consists of sources such as presidential security directives, accounts from intelligence personnel involved, Afghan narratives, embedded journalist accounts, Russian perspectives, and political interviews with leaders of the time to assist in suggesting massive U.S. influence in the failure of the U.S.S.R. This research is driven by three arguments: 1) U.S. involvement impacted détente in a manner which forced the Soviet Union into uncontrollable spending in hopes of expanding their empire, 2) U.S. aid to insurgent Afghans directly attributed to Soviet defeat and 3) U.S. involvement in the Soviet-Afghan War ultimately resulted in the downfall of the Soviet Union. Ultimately my argument is that U.S. involvement in the Soviet-Afghan War forced the Soviet Union into a political and economic situation from which it could not recover.